Assessment of quality of life and chronic pain in dogs. (September 2018) - Belshaw, Z.; Yeates, J.
Highlights: Quality of life assessment should be personal to each dog. Quality of life assessment has implicit limitations that can be minimised but not eliminated. Quality of life assessment must engage assessors. Reports on quality of life assessment should be explicit about what and how they assess. Abstract: Assessment of chronic pain and quality of life (QOL) are integral to clinical veterinary research and practice, and recent years have seen an increase in the published tools available for the assessment of both. However, the relationship between chronic pain and QOL in veterinary patients has received insufficient attention. This narrative review for the first time explores similarities, differences and interactions between chronic pain and quality of life and identifies common challenges to their assessment in dogs. In the opinion of these authors, assessments of both chronic pain and quality of life should be pro-active, global, regular, applied to answer specific questions for researchers and decision makers, and transparent about what has, and has not, been assessed. Collaboration in this field between animal welfare scientists, veterinary researchers and clinicians appears rare, and should be prioritised.